EUFOREA meeting on defining disease states in allergic rhinitis: towards a unified language in AR - Scadding, G. K.; Conti, D. M.; Scheire, S.; Backer, V.; Blaiss, M.; Cardell, L. O.; De Yun, W.; Ellis, A. K.; Fokkens, W.; Fox, A. T.; Gilbert Kruz, T.; Halken, S.; et al. (Frontiers in Allergy, 2025)
Allergic rhinitis (AR), the most prevalent immunological disease, affects approximately 400 million individuals globally and can significantly impact quality of life (QoL). Despite nearly 25 years of guidelines, AR remains largely under- diagnosed, suboptimally treated and poorly controlled. In the light of new knowledge and treatment options, there is a necessity to update or revise fundamental AR definitions to facilitate communication across diverse specialties engaged in its treatment and to improve patient care. The European Forum for Research and Education in Allergy and Airway Diseases (EUFOREA) convened a meeting of experts and patient representatives to deliberate the optimal methodology for measuring AR treatment responses and establishing novel treatment goals. This paper presents a consensus on revised AR definitions, including control, severe allergic rhinoconjunctivitis (SARC), refractory severe allergic rhinoconjunctivitis (R-SARC), remission, resolution, improvement, exacerbation, treatable traits (TTs), treat to target, relapse, progression, disease modification, and prevention.